A Method for the Immortalization of Newborn Mouse Skin Keratinocytes - Hammiller, Brianna O.; El-Abaseri, Taghrid Bahig; Dlugosz, Andrzej A.; Hansen, Laura A. (Frontiers in Oncology, 2015)
Isolation and culture of mouse primary epidermal keratinocytes is a common technique that allows for easy genetic and environmental manipulation. However, due to their limited lifespan in culture, experiments utilizing primary keratinocytes require large numbers of animals, and are time consuming and expensive. To avoid these issues, we developed a method for the immortalization of primary mouse epidermal keratinocytes. Upon isolation of newborn epidermal keratinocytes according to established methods, the cells were cultured long-term in keratinocyte growth factor-containing medium. The cells senesced within a few weeks and eventually, small, slowly growing colonies emerged. After they regained confluency, the cells were passaged and slowly refilled the dish. With several rounds of subculture, the cells adapted to culture conditions, were easily subcultured, maintained normal morphology, and were apparently immortal. The immortalized cells retained the ability to differentiate with increased calcium concentrations, and were maintained to high passage numbers, while maintaining a relatively stable karyotype. Analysis of multiple immortalized cell lines as well as primary keratinocyte cultures, revealed increased numbers of chromosomes, especially in the primary keratinocytes, and chromosomal aberrations in most of the immortalized cultures and in the primary keratinocytes. Orthotopic grafting of immortalized keratinocytes together with fibroblasts onto nude mouse hosts produced skin while v-rasHa infection of the immortalized keratinocytes prior to grafting produced squamous cell carcinoma. In summary, this method of cell line generation allows for decreased use of animals, reduces the expense and time involved in research, and provides a useful model for cutaneous keratinocyte experimentation.